PRAYING FOR PILGRIMS: WALIMATUSAFAR TRADITIONS AMONG INDONESIAN MUSLIMS - Mastanah; Mahsusi; Hudaa, Syihaabul; Ahmad Bahtiar (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
Walimatussafar is a tradition among Indonesians before performing the Hajj pilgrimage. However, this tradition requires a considerable amount of money as the tradition develops in the community. Walimatussafar traditions in Indonesia also vary with the many cultures of the people in Indonesia. The purpose of writing this article is to explain the various walimatussafar cultures that exist in Indonesia. The walimatussafar culture that exists in the community will be studied based on the aspects of whether it is good or not in the view of Islam. The research method used in this research is descriptive qualitative. Data collection conducted by researchers in the form of literature review, articles, books, and interviews with experts. Based on the research conducted by the researcher, it was found that the Javanese and Betawi tribes have different walimatussafar traditions. However, the meaning in it is the same, namely: praying, asking for forgiveness, asking to be prayed for, and asking for a smooth pilgrimage.